Performance improvement of synchronous generators through accurate modelling and integration of power electronics - Abu-Jalala, Al-Hussein (2021)
In this thesis, an active power filters (Shunt and series) are considered as an alternative to traditional methods (such as distributed winding, short pitch winding and skewing the stator) to improve the output power quality of synchronous generators. Instead of short pitching the winding, using different slot/pole combinations and/or skewing the stator, a power electronics device (active power filters) are used to improve the output power quality and the dynamic response of synchronous generators. A large amount of published work in the area of synchronous generator design has focused on traditional methods to improve the output power quality, but these methods complicate the synchronous generator, decrease generator rating and increase the manufacturing cost. In addition, the active power filters have been widely used in a power system to eliminate nonlinear load harmonics and reactive power compensation. The aim of this project is, therefore, to investigate using active power filters to improve the output power of a simple design of synchronous generator and improve the dynamic response of the synchronous generator without damper bars. Using an active power filters in parallel and series with a simplified synchronous generator allows the use of simple generator designs with reduced complexity and manufacturing cost, without compromising the quality of power delivered to the load. A simplified synchronous generator is proposed in this thesis to investigate the project idea, this generator has a full pitch-winding configuration and unskewed stator to increase generator power and simplify the manufacturing process. A two converters are connected one in parallel and one in series with the proposed generator to achieve IEEE standards for current harmonics. This thesis describes the derivation of the proposed synchronous generator model and active power filters control as well as experimental results from the proposed generator. Simulation and experimental results are provided to validate the approach and to demonstrate the feasibility of the proposed synchronous generator with active power filters modelling approach and control strategy. A good correlation between simulation and experimental results was obtained.